Mycelial culture extracts of selected wood-decay mushrooms as a source of skin-protecting factors - Sułkowska-Ziaja, Katarzyna; Grabowska, Karolina; Apola, Anna; Kryczyk-Poprawa, Agata; Muszyńska, Bożena (Biotechnology letters, 2021)
Objectives This study analyzed the content of substances with cosmetologic properties in the extracts obtained from the mycelial cultures of Ganoderma applanatum , Laetiporus sulphureus , and Trametes versicolor . The effect of these extracts on the inhibition of tyrosinase and hyaluronidase was determined, and their values of sun protection factor (SPF) were calculated. Results The total amount of phenolic acids in the extracts ranged from 2.69 ( G. applanatum ) to 10.30 mg/100 g dry weight ( T. versicolor ). The total amount of sterols was estimated at 48.40 ( T. versicolor ) to 201.04 mg/100 g dry weight ( L. sulphureus ), and that of indoles at 2.90 ( G. applanatum ) to 16.74 mg/100 dry weight ( L. sulphureus ). Kojic acid was determined in the extracts of L. sulphureus and G. applanatum . It was observed that L. sulphureus extract caused dose-dependent inhibition of hyaluronidase, while all the extracts inhibited tyrosinase. The extract of G. applanatum exhibited an SPF value of ~ 9. Conclusions The results showed that the mycelial cultures of the studied species may be used as an alternative source of substances used in cosmetology.